The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1981
DOI: 10.1139/b81-287
|View full text |Cite
|
Sign up to set email alerts
|

Use of plants for food and medicine by Native Peoples of eastern Canada

Abstract: At least 175 food plants and 52 beverage plants were gathered by Native Peoples in eastern Canada. Iroquoian agriculturalists of southern Ontario cultivated corn, beans, squash, tobacco, and sunflowers, and gathered the greatest variety of food plants. Southern and eastern Algonkian hunters and gatherers ate a wide variety of wild plant foods including fleshy fruits, nuts, greens, and underground parts. Little is known about the use of wild food plants by northern Cree and Naskapi.Nutritional data for gathered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(114 citation statements)
references
References 0 publications
1
113
0
Order By: Relevance
“…In contrast, Arnason et al (1981) suggested an earlier introduction and described the extensive use of various Brassica and Sinapis spp. for food and medicine by native peoples of eastern Canada.…”
Section: Historymentioning
confidence: 99%
“…In contrast, Arnason et al (1981) suggested an earlier introduction and described the extensive use of various Brassica and Sinapis spp. for food and medicine by native peoples of eastern Canada.…”
Section: Historymentioning
confidence: 99%
“…When the bioactivities of extracts made from separated organs of the same species (i.e., root, stem, leaf, and fruit extracts) were compared, certain plants exhibited organ-specific activities , some of which could be attributed to differences in phenolic constituents within the plant organs (Harris et al, 2007). Here, we extend these findings to an analysis of minhikw, the Cree term for Picea glauca, a plant reported useful for controlling diverse diabetic complications among several First Nations groups (Arnason et al, 1981;Leduc et al, 2006), particularly the Cree of Whapmagoostui. We report that polar fractions of Picea glauca (minhikw) needle are more effective than bark and cone extracts at protecting PC12 peripheral neuronal precursors from both glucose toxicity and glucose deprivation.…”
Section: Introductionmentioning
confidence: 63%
“…As reviewed by Arnason et al (1981) as well as by Moerman (1988), the needles, cones, and bark are used separately by various First Nations groups of eastern Canada to treat different symptoms, including those associated with diabetes and its related complications (Arnason et al, 1981;Moerman, 1988;McCune & Johns, 2002). For instance, the cone and bark (gum) are prepared by the Abenaki for frequent urination whereas the Mi'kmaq and Atikamekw employ the bark to treat sores and wounds.…”
Section: Discussionmentioning
confidence: 99%
“…The ethnopharmacological study conducted by Arnason et al (Arnason, Hebda, & Johns, 1981) has collected extensive data on this species. Several Native American First Nations consumed the gum-resin of various spruce species for chewing.…”
Section: Picea Traditional Usesmentioning
confidence: 99%
“…In Europe, a spruce species -Picea abies -was commonly used in medicinal baths to treat rheumatisms and nervous disorders; to this effect, young shoots and needles of 60 to 80 year old trees were preferably harvested for their inherently high concentration of active ingredients. Table 2 summarizes the main ethnopharmacological data published by Arnason et al (Arnason et al, 1981) with regards to the Picea genus in Québec. Reported therapeutic uses of any particular forest species often yield valuable information to help identify bioactive components of extractives, for future applications in nutrition, cosmetics, cosmeceuticals, pharmaceuticals, etc.…”
Section: Picea Traditional Usesmentioning
confidence: 99%